Divergent lncRNA GATA3-AS1 Regulates GATA3 Transcription in T-Helper 2 Cells - Gibbons, Hunter R.; Shaginurova, Guzel; Kim, Laura C.; Chapman, Nathaniel; Spurlock, Charles F.; Aune, Thomas M. (Frontiers in Immunology, 2018)
Long non-coding RNAs (lncRNAs) possess a diverse array of regulatory functions including activation and silencing of gene transcription, regulation of splicing, and coordinating epigenetic modifications. GATA3-AS1 is a divergent lncRNA gene neighboring GATA3. GATA3 is considered the master regulator of TH2 lineage commitment enabling TH2 effector cells to efficiently transcribe genes encoding cytokines IL-4, IL-5, and IL-13. Here, we show that the GATA3-AS1 lncRNA is selectively expressed under TH2 polarizing conditions and is necessary for efficient transcription of GATA3, IL5, and IL13 genes, while being sufficient to induce GATA3 expression. GATA3-AS1 is required for formation of permissive chromatin marks, H3K27 acetylation and H3K4 di/tri-methylation, at the GATA3-AS1-GATA3 locus. Further, GATA3-AS1 binds components of the MLL methyltransferase and forms a DNA-RNA hybrid (R-loop) thus tethering the MLL methyltransferase to the gene locus. Our results indicate a novel regulatory function for a divergent lncRNA and provide new insight into the function of lncRNAs in T helper cell differentiation.